Estimation of the gas hydrate saturation from multichannel seismic data on the western continental margin of the Chukchi Rise in the Arctic Ocean - Choi, Yeonjin; Kang, Seung-Goo; Jin, Young Keun; Hong, Jong Kuk; Shin, Sung-Ryul; Kim, Sookwan; Choi, Youngil (Frontiers in Earth Science, 2022)
A multichannel seismic survey was conducted to investigate the geophysical characteristics of gas hydrates along the western continental margin of the Chukchi Rise around an ARAON mound cluster, which was first recovered in 2016. In the seismic data, gas hydrate-related bottom simulating reflection (BSR) was widely distributed along the western continental margin of the Chukchi Rise. High-precision seismic P- wave velocity was obtained to investigate the geophysical characteristics of the gas hydrate structures in the BSR areas. Iterative migration velocity analysis (IMVA) was used to construct a detailed P-wave velocity model from the acquired seismic data. The gas hydrate and free gas layers have abnormally high- and low-seismic P-wave velocities; the precise velocity model allows us to understand the detailed spatial distribution of gas hydrate and free gas structures. The effective medium theory (EMT) model enables estimations of the saturation of gas hydrates from constructed seismic P-wave velocity model. We propose the P-wave velocity and gas hydrate saturation models from acquired multichannel seismic data and estimate the total amount of methane in the western continental margin of the Chukchi Rise for the first time.